A systematic review and meta-analysis examining the effect of stress at encoding on line-up performance - Gering, Milton Anthony (Department of Psychology, 2022)
Although much research has been conducted on the effect of stress on eyewitness memory, the answer to this question remains unclear. Whereas a previous meta-analysis (Deffenbacher et al., 2004) concluded that stress negatively affects eyewitness identification ability, recent studies have shown a lack of consensus. As most crimes are stressful events and eyewitness evidence is influential in courts; clarity on the effect of stress is important to legal systems around the world. It is difficult to summarise extant research as many studies use differing methods making the source of disagreement unclear. Added to that, many studies report insufficient detail needed to judge the rigour of research designs, and thus the effects of stress. The present systematic review attempts to synthesise the literature and presents an analysis using recent meta-analytic techniques that allow for the influence of moderator variables to be quantified. It shows that the effect of stress at encoding on line-up decisions is not clear, with studies reporting both positive and negative effects, and examines reasons for differences in effects found between studies. A finding of note is that sequential or simultaneous line-up presentation has a moderating effect of stress on line-up performance. Additionally, a multilevel model shows that using continuous, rather than dichotomous, measures of stress may clarify the stress-performance relationship. Recommendations for further research are made in the hope that new studies can answer the important question of whether witnesses who experience high levels of stress at encoding are likely to make better or worse line-up decisions.